Differential effects of age at illness onset on verbal memory functions in antipsychotic-naïve schizophrenia patients aged 12–43 years - Fagerlund, Birgitte; Pantelis, Christos; Jepsen, Jens Richardt Møllegaard; Raghava, Jayachandra Mitta; Rostrup, Egill; Thomas, Marie Bjerregaard; Nielsen, Mette Ødegaard; Bojesen, Kirsten; Jensen, Karsten Gjessing; Stentebjerg-Decara, Marie; Klauber, Dea Gowers; Rudå, Ditte; et al. (Psychological medicine, 2021)
The typical onset of schizophrenia coincides with the maturational peak in cognition; however, for a significant proportion of patients the onset is before age 18 and after age 30 years. While cognitive deficits are considered core features of schizophrenia, few studies have directly examined the impact of age of illness onset on cognition. The aim of the study was to examine if the effects of age on cognition differ between healthy controls (HCs) and patients with schizophrenia at illness onset. We examined 156 first-episode antipsychotic-naïve patients across a wide age span (12-43 years), and 161 age- and sex-matched HCs. Diagnoses were made according to ICD-10 criteria. Cognition was assessed using the Brief Assessment of Cognition in Schizophrenia (BACS), and IQ was estimated using subtests from the Wechsler adult- or child-intelligence scales. Multivariate analysis of covariance (MANCOVA) was used to examine linear and quadratic effects of age on cognitive scores and interactions by group, including sex and parental socioeconomic status as covariates. There was a significant overall effect of age on BACS and IQ (p < 0.001). Significant group-by-age interactions for verbal memory (for age-squared, p = 0.009), and digit sequencing (for age, p = 0.01; age-squared, p < 0.001), indicated differential age-related trajectories between patients and HCs. Cognitive functions showing protracted maturation into adulthood, such as verbal memory and verbal working memory, may be particularly impaired in both early- and late-schizophrenia onset. Our findings indicate a potential interaction between the timing of neurodevelopmental maturation and a possible premature age effect in late-onset schizophrenia.